Enhancing students' creative thinking skills through creative problem solving in green schools: A sustainable approach to learning - Pratama, Anisa O. S.; Handoko, Akbar; Kuswanto, Eko; Asnawi, Daffa Rahmanda (Assimilation: Indonesian Journal of Biology Education, 2025)
This research aims to analyze the influence of the Creative Problem Solving model on the creative thinking skills of class XII high school students. This research uses a quantitative approach with a quasi-experimental design, specifically the matched-only pretest-posttest control group design. The population in this study consisted of 167 students. The research sample was obtained using the cluster random sampling technique, resulting in an experimental class of 34 students and a control class of 34 students. The instruments used were tests, questionnaires, observation sheets, and documentation. The collected data was analyzed using the MANOVA test. The results show that the N-Gain value for creative thinking skills in the experimental class is higher than in the control class, specifically 0.58 0.36. Therefore, it can be concluded that using the Creative Problem Solving learning model significantly influences the creative thinking skills of class XII high school students.